Techno-Economic Analysis of the Implementation PV Rooftop System at the Denpasar Mayor's Office Building - putra, i wayan swi; Kumara, I Nyoman Satya; Hartati, Rukmi Sari (Majalah Ilmiah Teknologi Elektro, 2022)
Indonesia is located along the equator so that it has a huge potential for solar energy, but it has not been able to be utilized optimally to reduce the use of fossil energy that is not environmentally friendly. In order to increase the use of new and renewable energy by 23% in 2025 where the target for the utilization of solar energy is 6.5 GW, the Government through the National Energy Council issued a policy to encourage each region to accelerate the utilization of solar energy in accordance with the mandate of the General National Energy Plan which requires the use of a minimum of 30% of the roofs of government buildings for the use of solar PV rooftop. The Denpasar City Government in implementing the Bali Provincial Energy General Plan can implement solar PV rooftop system at the Denpasar Mayor's Office Building as a pilot project for government buildings in Denpasar City. From the results of technical studies that have been carried out, the Denpasar Mayor's Office Building has a total roof area of ??1,732.14 m2. However, based on the Minister of Energy and Mineral Resources No. 49/2018, in this study designed solar PV rooftop with a capacity of 112.5 kWp. Solar PV rooftop simulation with PVSyst produces an average annual performance potential of 81.6% with an annual energy production of 175 kWh. Solar PV rooftop  which is designed can save the use of PLN's electrical energy by 72.12% in a year. The results of the design are then tested economically using the NPV, IRR, BCR, PI and PP methods. NPV is positive at discount rates of 6%, 10%, and 15%. The IRR test is worth 20.12%, the BCR test is 14.57, the PI test is 7.31 and the PP test states that this investment requires a period of 3.4 years to return the initial capital. Based on the technical and economic analysis, the design of solar PV rooftop on the roof of the Denpasar Mayor's Office is very feasible because it is able to produce electrical energy that can save significant use of PLN's electrical energy and meet the investment eligibility criteria.